2023
DOI: 10.1002/adma.202310279
|View full text |Cite
|
Sign up to set email alerts
|

Eco‐Friendly Solvent Engineered CsPbI2.77Br0.23 Ink for Large‐Area and Scalable High Performance Perovskite Solar Cells

Seid Yimer Abate,
Yifang Qi,
Qiqi Zhang
et al.

Abstract: The performance of large‐area perovskite solar cells (PSCs) has been assessed for typical compositions, such as methylammonium lead iodide (MAPbI3), using a blade coater, slot‐die coater, solution shearing, ink‐jet printing, and thermal evaporation. However, the fabrication of large‐area all‐inorganic perovskite films is not well developed. This study develops, for the first time, an eco‐friendly solvent engineered all‐inorganic perovskite ink of dimethyl sulfoxide (DMSO) as a main solvent with the addition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The selection criteria for solvents capable of dissolving perovskites are based on the dielectric constant and Gutmann donor number. 25,26 The dielectric constant reflects the ability of a solvent to dissolve ionic compounds, while the Gutmann donor number describes the ability of a solvent to coordinate with cations. Solvents with a low Gutmann donor number would weakly coordinate with divalent metal centers and thus tend to form large molecular clusters.…”
Section: Resultsmentioning
confidence: 99%
“…The selection criteria for solvents capable of dissolving perovskites are based on the dielectric constant and Gutmann donor number. 25,26 The dielectric constant reflects the ability of a solvent to dissolve ionic compounds, while the Gutmann donor number describes the ability of a solvent to coordinate with cations. Solvents with a low Gutmann donor number would weakly coordinate with divalent metal centers and thus tend to form large molecular clusters.…”
Section: Resultsmentioning
confidence: 99%
“…To address the issue of instability, it is suggested that the organic cations be replaced with all inorganic Cs + to create CsPbX 3 (X = I − , Br − , Cl − or their mixtures) [14][15][16][17][18]. CsPbX 3 typically has four types of crystal structures, including the cubic structure (α-, Pm3m), the tetragonal structure (β-, P4/mbm), the orthorhombic structure (γ-, Pbnm), and a nonperovskite structure (δ-, Pnma) [19].…”
Section: Introductionmentioning
confidence: 99%